Studi Literatur: Implementasi Teori Akuntansi Pada Laporan Keuangan Sektor Publik - Annisa Handayani; Juanda Maulana; Putri Kemala Dewi Lubis (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Developing accounting theory is very important in making financial reports. Accounting theory is an arrangement of concepts, definitions and propositions that presents a systematic picture of accounting phenomena, as well as explaining the relationships between variables in the accounting structure. This research uses qualitative research methods. The data collection technique uses secondary data which is carried out by literature review and literature study. The results of this study state that the benefits of public sector accounting are indeed very important in preparing financial reports with standard account classifications, recording and journaling procedures that are in accordance with the business circulation of public sector organizations including interpretation, treasury and accounting reports. The standards belonging to public sector financial accounting have been created and developed accordingly according to internationally accepted standards to achieve stable and comparable accounting functionality for all countries or jurisdictions.